Determinants of dividend policy in ASEAN-5 - Chong, Boon Chiew (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study provides evidence of dividend payout policy by ASEAN-5 (Malaysia, Indonesia, Philippines, Singapore and Thailand) firms during the period from 2000-2009. The number of listed firms paying dividends has declined significantly in recent years. This might be due to the increasing number of nonpayers that includes former payers and firms that never paid during the study period. Nevertheless, upon applying the portfolio approach of Fama and French (2001), we find evidence that offers hints of a decline in the propensity to pay dividends in some of the sample countries, particularly among those firms that are at the margin for paying dividends. From the univariate analysis, the evidence suggests that five fundamentals such as profitability, firm size, growth opportunities, leverage and earned equity are main factors in the decision to pay dividends among the ASEAN-5. The empirical result from the logit regression model shows that those firms paying dividends are larger, more profitable, have a substantially higher ratio of retained earnings to common shareholder equity and have less debt ratio as well as growth options than non-dividend-paying firms. These results are in line with Fama and French (2001) and Eije and Megginson (2008). To some extent, the empirical evidence does not concentrate on signaling theory for the propensity to pay dividend but strongly supports the life cycle theory from DeAngelo et al. (2006). In addition, consistent with Lintner (1956), the study also shows that dividend policies in all countries exhibit stickiness characteristics. However, there still exist several different characteristics of dividend payers and non-payers among the countries represented in the study.